Literature review on earthen vernacular heritage: contributions to a referential framework - Gilberto, Carlos (2022)
The state of the art of earthen architecture and vernacular built heritage comprises a complex set of issues that range from fundamental problematic recognition to anthropological and cultural studies and, more recently, to technological and experimental analyses. This paper addresses the development of the field, following the milestones of the international literature and pursuing a reflective-theory approach within a historical framework. It aims to explore the main contributions that have enhanced vernacular heritage and earthen architecture as specific domains, from pioneering public awareness essays to institutional expertise guidelines. Finally, in addition to the literature review process, this paper considers the recent corpus of recommendations from conservation management reference institutions, the updating of the operative problematic of earthen vernacular built heritage, and the relevance of local community involvement in facing increasing challenges.